Dual Invasive Pulmonary Mycosis in a Post Covid-19 Patient: An Autopsy Diagnosis - Taneja, Nitin Sagar; Jadhav, Toyaja M; Das, Debasheesh; Sen, Alok D (Annals of Pathology and Laboratory Medicine, 2024)
Patients suffering from Covid19 associated lower respiratory tract infection are most often in an immunocompromised state and are indeed vulnerable to a host of bacterial and fungal infections. Among the fungi, common invaders include candidiasis, aspergillosis and mucormycosis. Aspergillosis is a relatively common fungal infection which has been widely reported to occur in patients suffering from or recently recovered Covid19 infection. The invasive form of this fungus, is, however, less commonly reported in literature. Invasive pulmonary mucormycosis is a relatively uncommon pulmonary fungal disease. Its early diagnosis is essential but difficult as it lacks an effective treatment protocol. Commonly affecting a primarily immunocompromised host, the diagnosis of both infecting fungi primarily rests upon detection of their hyphae and/or spores in the lung and vascular tissue. This report describes presence of invasive pulmonary mucor and aspergillosis detected at autopsy in a post covid 19 patient, who presented with a naso-orbital swelling and had a rather silent clinical course followed by sudden onset of a single episode of massive hemoptysis resulting in his death.